2019
DOI: 10.1039/c9ta01049a
|View full text |Cite
|
Sign up to set email alerts
|

Surface reorganization engineering of the N-doped MoS2 heterostructures MoOx@N-doped MoS2−x by in situ electrochemical oxidation activation for efficient oxygen evolution reaction

Abstract: The unique heterostructure MoOx@N-doped MoS2−x was performed in situ by electrochemical oxidation, which showed remarkable OER activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…Currently, there are some studies reporting about doped MoS 2 serving as an adsorbent and a sensor [19][20][21][22][23]. It is reported that Ni-MoS 2 shows strong adsorption to O 2 [24][25][26][27][28][29][30][31][32][33]. Ni-doped MoS 2 film sensors have been verified to be a suitable candidate to detect SO 2 , one typical decomposition product of SF 6 [34].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are some studies reporting about doped MoS 2 serving as an adsorbent and a sensor [19][20][21][22][23]. It is reported that Ni-MoS 2 shows strong adsorption to O 2 [24][25][26][27][28][29][30][31][32][33]. Ni-doped MoS 2 film sensors have been verified to be a suitable candidate to detect SO 2 , one typical decomposition product of SF 6 [34].…”
Section: Introductionmentioning
confidence: 99%
“…Lately, many researchers have tried to develop TMDs as stable and highly active OER catalysts for overall water splitting. [ 22–39 ] To impart such bifunctional catalytic activity, first transition metals such as Co and Ni are frequently incorporated in various approaches, including doping in the ionic form. Yet, there have been only a few studies on the bifunctional catalytic activity of the 1T (or 1T′) phase MoS 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen doping in MoS 2 was carried out via in situ electrochemical oxidation process and it was coupled to MoOx to form the hybrids. These electrodes were tested for OER, which exhibited an excellent electrocatalytic activity with a low overpotential of 270 mV at 10 mA cm −2 , a small Tafel slope of 61 mV dec −1 , and satisfactory stability . Edge contact geometry is adopted in the formation of well‐defined and mixed dimensional W 17 O 47 –MoS 2 heterostructures.…”
Section: Applications Of Mos2 For Energy Conversion and Storagementioning
confidence: 99%